Metastatic Adenocarcinoma of Prostate posing as upper tract ureteral mass - Sah, Anil Kumar; Maharjan, Bipin; Adhikari, Mahesh Bahadur; Rana, Reena; Panth, Rajesh; Aryal, Gopi (Nepalese Journal of Cancer, 2021)
Prostate cancer metastasis to the ureter is extremely rare because only 45 such cases have been reported worldwide in the last century. It accounts for 30% of ureteral metastasis. Neuroendocrine differentiation is approximately 1% of the entire primary prostate adenocarcinoma pathology. Metastatic prostate cancer may pose as upper tract urothelial carcinoma. Prostate may look normal on clinic-radiological examination in prostate cancer. Majority of such cases are managed with nephroureterectomy. Herein, we report a case of 62-year gentleman, who presented with refractory left flank pain with repeated imaging suggestive of neoplastic left ureteric stricture and normal prostate on clinic-radiological examinations. The case was later found with the diagnosis of metastatic prostate adenocarcinoma with neuroendocrine differentiation after left sided nephroureterectomy done for a provisional diagnosis of Upper Tract Urothelial Carcinoma (UTUC).